Estrategia de desarrollo sostenible para la regeneración urbana de la franja turística de la Parroquia El Rosario del Cantón Guano - Velasteguí Padilla, Gladys Liliam (2021)
Urban regeneration as a sustainable development strategy made it possible to identify the waste of a public space with a high level of tourism due to the lack of collective awareness and proper planning of the urban area, the general objective of this study is to design a sustainable development strategy that contribution to the urban regeneration of the tourist strip of the El Rosario Parish of the Guano Canton; The methodology used is based on a descriptive study based on the quantitative approach, the research method was deductive and the technique used for the collection of information was the survey and the observation that allowed the planimetric and topographic survey to delimit three areas of intervention: conservation, regeneration and revitalization that had an urban treatment through the urban acupuncture technique, seeking to globalize the collective consciousness towards a common goal. The diagnostic results determined the low citizen participation, lack of empowerment of the space and of regulations to regulate the public space. With the implementation of the regeneration of this area, priority is given to the design and planning of a renovated space that will generate sources of employment and develop the local economy, using renewable energy and urban facilities with recyclable materials, improving the quality of life of the inhabitants of the area. immediate and immediate environment. The intervened area to be repontentialized will generate a tourism that will increase the social, economic and cultural of the canton.